2019
DOI: 10.1590/1678-7757-2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Aloe vera with mesenchymal stem cells from dental pulp on bone regeneration: characterization and treatment of non-critical defects of the tibia in rats

Abstract: Objective This study aimed to evaluate the inflammatory effect and bone formation in sterile surgical failures after implantation of a collagen sponge with mesenchymal stem cells from human dental pulp (hDPSCs) and Aloe vera . Material and Methods Rattus norvegicus (n=75) were divided into five experimental groups according to treatment: G1) control (blood clot); G2) Hemospon ® ; G3) Hemospon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
2
20
0
2
Order By: Relevance
“…The histological evaluation was performed for a total of 28 of the selected papers (93.3%) [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] and histomorphometry was conducted in 25 of the studies’ experiments [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] (83.3%). For a total of 18 studies (60%) micro-CT evaluation was performed [ 44 , 45 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The histological evaluation was performed for a total of 28 of the selected papers (93.3%) [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] and histomorphometry was conducted in 25 of the studies’ experiments [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] (83.3%). For a total of 18 studies (60%) micro-CT evaluation was performed [ 44 , 45 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 articles were conducted on rat models and the DPSC culture passage ranged from one to six [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. A total of 14 papers were conducted on rat calvaria/critical size defects [ 46 , 47 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 58 , 60 , 62 ], 2 on dental alveolar defects/maxillary [ 44 , 61 ], 2 on dental alveolar defects/mandibular and 1 article studied tibial bone defects [ 45 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, MSCBMsu showed a logarithmic increase over nine days before showing a reduction in cell concentration ( Figure 1 ). This characteristic is not uncommon among mesenchymal stem cell lines, and studies with bone marrow, adipose tissue, and dental pulp lineages have commonly demonstrated similar evidence [ 33 35 ]. This observation raises the possibility that this group of somatic stem cells may present relevant metabolic adaptability.…”
Section: Discussionmentioning
confidence: 85%
“…Sparse cell conditions are more suitable for hard tissue regeneration to maintain the osteoblast and chondrocytes differentiation potential of DPSCs [20]. Isolated heterozygous cell population contain not only DPSCs, but also other types of cells that adhere to plastic, therefore only CD29, CD44, CD105 and STRO-1 positive cells are selected by fluorescence activating cell sorting (FACS), or alternatively magnetic activated cell sorting (MACS) [20,26]. Single Cell Raman Spectroscopy (SCRM) is the first tool to accurately discriminate and select for best quality DPSCs, improving the efficiency of stem cell therapy [27].…”
Section: Culture and Isolationmentioning
confidence: 99%